Shaping the Future of ICT Research. Methods and Approaches IFIP WG 8.2, Working Conference, Tampa, FL, USA, December 13-14, 2012. Proceedings - Bhattacherjee, Anol.; Fitzgerald, Brian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the IFIP WG 8.2 Working Conference "Shaping the Future of ICT Research", held in Tampa, FL, USA, in December 2012. The 15 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in the following topical sections: new methods in design science research; recent developments in inductive research methods; emerging themes in interpretive case study research; new ideas in positivist research; and innovative trends in information systems research.
Resolving Name Conflicts for Mobile Apps in Twitter Posts -- Using Adjective Features from User Reviews to Generate Higher Quality and Explainable Recommendations -- Product Semantics in Design Research Practice -- Action Design Ethnographic Research (ADER): Vested Interest Networks and ICT Networks in Service Delivery of Land Records in Bangladesh -- Grounded Analytic Research: Building Theory from a Body of Research -- Using Photo-Diary Interviews to Study Cyborgian Identity Performance in Virtual Worlds -- Living in a Sociomaterial World -- Co-materialization: Digital Innovation Dynamics in the Offshore Petroleum Industry -- Mutability and Becoming: Materializing of Public Sector Adoption of Open Source Software -- Moderating Effect of Environmental Factors on eHealth Development and Health Outcomes: A Country-Level Analysis -- Social Networks and Communication Media for Generating Creative Ideas -- Cultural Challenges in Information Systems Innovation: The Need for Differentiation Studies -- Digital Artifacts as Institutional Attractors: A Systems Biology Perspective on Change in Organizational Routines -- Amazon Mechanical Turk: A Research Tool for Organizations and Information Systems Scholars -- Customization of Product Software: Insight from an Extensive IS Literature Review.
Keywords: Computer science; Computers; Application software; Computers and civilization; Management information systems; Computer Science; Management of Computing and Information Systems; Computers and Society; Computer Applications; Information Systems and Communication Service; Information Systems Applications (incl. Internet).; Models and Principles; Electronic books